Analisis Tingkat Kesehatan Bank Menggunakan Metode Pendekatan Risk Profile, Good Corporate Governence, Earning, Capital (RGEC) Pada PT. BPR BKK Wonogiri (Perseroda) - Rizki Kurnia Sulistyo; Susilaningtyas Budiana Kurniawati; Istinganah Eni Maryanti (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the soundness level of PT BPR BKK Wonogiri (Perseroda) using the Risk Profile, Good Corporate Governance, Earnings, and Capital (RGEC) approach during the 2022–2024 period. The research is motivated by the increasing banking business risks, particularly in Rural Banks (BPR), following the COVID-19 pandemic, which affected asset quality, profitability, and capital adequacy. This study employs a quantitative descriptive method using secondary data derived from financial statements and Good Corporate Governance (GCG) reports. The analysis measures Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) for the Risk Profile factor, self-assessment results for GCG, Return on Assets (ROA), Net Interest Margin (NIM), and Operating Expenses to Operating Income (BOPO) for the Earnings factor, and Minimum Capital Adequacy Requirement (KPMM) and Core Capital to Non-Performing Productive Assets (MIAPB) ratios for the Capital factor. The results indicate that the composite soundness level of PT BPR BKK Wonogiri (Perseroda) during the study period falls into the “sound” category, supported by a manageable risk profile, adequate governance implementation, stable profitability performance, and sufficient capital to absorb potential risks. This research is expected to contribute theoretically to the development of bank soundness assessment studies using the RGEC approach and practically serve as an evaluation reference for management and regulators in improving the stability and performance of rural banks.